COMMUNICATIVE GRAMMAR IN ENGLISH LANGUAGE CLASSES - Ruziev Khusniddin Bakhritdinovich (Web of Journals Publishing, 2024)
This article deal with communicative grammar in English language classes. The advantages of teaching English language classes through communicative grammar are discussed.
Keywords: communicative grammar, contextualization, whole-class grouping, class observation guide.